INTENSIFICATION OF «LIVING KNOWLEDGE» AT THE TRANSITION TO «KNOWLEDGE SOCIETY»: PROJECT AND REALITY - Naira V. Danielyan (Высшее образование в России)
The article studies the «knowledge society» concept with the regard to the modern tendencies in the system of Russian higher education. Due to a broader application of distant technologies in educational process and the reduction of lectures and practical classes aimed at the acquisition of «living knowledge», i.e. an individual's definite knowledge, it becomes harder and harder for universities to train a specialist who is capable to produce some intellectual capital on the basis of his personal self-improvement, intellectual power and imagination. As a decision, it's offered to use the combined approach. It allows applying distant technologies as an important auxiliary tool that simplifies significantly the process ofgetting a new knowledge by a student. Nowadays, owing to fast changes of all life aspects, the educational process is considered as a lifelong personal self-training based on cooperation and communication. Subjectivity as a «self-investing» process turns into the main feature of knowledge productivity. The author concludes that higher school training should include «living», common knowledge as well as mankind humanitarian values, an individual's creative potential, imagination and emotions, accompanied by his informal knowledge. Neither technological nor computerized educational approaches can give the same results.